2008
DOI: 10.1002/micr.20485
|View full text |Cite
|
Sign up to set email alerts
|

Developments in perforator imaging for the anterolateral thigh flap: CT angiography and CT‐guided stereotaxy

Abstract: CT Angiography and CT-guided stereotaxy are useful adjuncts to Doppler ultrasound for imaging perforators prior to ALT flaps. A larger study is suggested to quantify the accuracy of these techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 12 publications
(7 reference statements)
0
40
0
2
Order By: Relevance
“…3) and to demonstrate the volume, shape, and location of bone to be harvested preoperatively, as a guide to surgical approach. In addition to previous studies demonstrating that CTA is more accurate than ultrasound in flap planning, 8,15 the volumetric and structural analysis of iliac bone provides a further extension of the role of CTA over other imaging modalities.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3) and to demonstrate the volume, shape, and location of bone to be harvested preoperatively, as a guide to surgical approach. In addition to previous studies demonstrating that CTA is more accurate than ultrasound in flap planning, 8,15 the volumetric and structural analysis of iliac bone provides a further extension of the role of CTA over other imaging modalities.…”
Section: Discussionmentioning
confidence: 93%
“…8 A vascularized bone flap is thus preferred with vascularized proximal fibular described previously for distal radius reconstruction. 12 The major limitation of the use of fibular bone (as a flap or graft) is that it consists mostly of cortical bone with resultant poor osteogenicity and may be considered an inferior choice in the setting of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The use of preoperative CT has also been shown to significantly reduce operative times in select studies (17). Accuracy can be further improved with stereotactic localization, however, this technology is not widely available and is still based on a CT scan taken pre-operatively (6, 7). …”
Section: Discussionmentioning
confidence: 99%
“…Newer techniques such as CT and MRI have been described for pre-operative perforator identification and initial studies have shown potential for decreased operative times and complications (2-5). Stereotactic image-guided perforator imaging has also been described as a more accurate planning modality; however, it is still based on a pre-operative CT scan and its practical utility is limited (6,7). These techniques all evaluate perforators in the pre-operative planning phase as a majority of surgeons still rely on intraoperative clinical assessment of vessel size and location as the final determining factor.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated the superiority of computed tomographic angiography (CTA) over the other options for the preoperative mapping in the perforator flaps because it could evaluate the perforators more precisely. 1 Nevertheless, CTA has a disadvantage that it cannot be used in real time and provide real-time feedback during harvesting flap. Color Doppler sonography is another effective tool for surgical planning.…”
mentioning
confidence: 99%